1996
DOI: 10.1007/bf01372110
|View full text |Cite
|
Sign up to set email alerts
|

Hypomelanosis of lto associated with neuroblastoma

Abstract: We report a patient with hypomelanosis of Ito associated with neuroblastoma. Though not previously reported, the association is plausible since both conditions are forms of "neurocristopathy".

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…2,8,18Kyphoscoliosis or scoliosis not requiring surgery, pectus excavatum, and carinatum are other relatively common findings as are small hands and feet, pes valgus or varus, genu valgus, or congenital hip dislocation. Occasional patients can mosaic chromosomal abnormalities were found, whereas no chromosomal mosaic could be found in the blood and tumor karyotypes in the medulloblastoma reported bySteiner et al2o No genetic data were reported in the remnants 58,59,91,92,94.…”
mentioning
confidence: 91%
“…2,8,18Kyphoscoliosis or scoliosis not requiring surgery, pectus excavatum, and carinatum are other relatively common findings as are small hands and feet, pes valgus or varus, genu valgus, or congenital hip dislocation. Occasional patients can mosaic chromosomal abnormalities were found, whereas no chromosomal mosaic could be found in the blood and tumor karyotypes in the medulloblastoma reported bySteiner et al2o No genetic data were reported in the remnants 58,59,91,92,94.…”
mentioning
confidence: 91%
“…162 Rarely, malignant tumors such as acute lymphoblastic leukemia, 163 medulloblastoma, and neuroblastoma have been reported. 164,165 In 2011, El-Sawy et al reported on a child patient presenting with unilateral leukocoria, who was ultimately diagnosed with retinoblastoma. 166…”
Section: Hypomelanosis Of Ito and Tumorsmentioning
confidence: 99%
“…Incontinentia pigmenti acromians (hypomelanosis of Ito) is associated with neuroblastoma (Oguma et al, 1996); the adrenal medulla and sympathetic chain from which neuroblastomas arise are neural crest derivatives. Incontinentia pigmenti acromians (hypomelanosis of Ito) is associated with neuroblastoma (Oguma et al, 1996); the adrenal medulla and sympathetic chain from which neuroblastomas arise are neural crest derivatives.…”
Section: Genetics Of Neurocutaneous Syndromesmentioning
confidence: 99%